The behavior of logistic equation with alley effect in fuzzy environment: fuzzy differential equation approach - Salahshour, Soheil; Ahmadian Hosseini, Syed Ali; Mahata, Animesh; Mondal, Sankar Prasad; Alam, Shariful (Springer Verlag, 2018)
In this paper a fuzzy logistic equation with alley effect is introduced by considering some parameter as fuzzy numbers. Due to presence of the fuzzy number the corresponding differential equation in logistic equation model with alley effect becomes fuzzy differential equation. Considering generalized Hukuhara derivative approach the fuzzy logistic equation converted to system of two crisp differential equations. We obtain the conditions of stability criterion for different cases. Different numerical examples are given to support our work.